Nakhijevan from the Treaty of Batum and the Military Campaign of A. Ozanian to "Republic of Arasdayan" - Majid Karimi (ՀՀ ԳԱԱ)
1918 թ. փետրվարի 10-ից Կովկասյան ճակատում հաջողությամբ ծավալված թուրքական հարձակումը հանգեցրեց 1918 թ. մարտի 3-ին կնքված Բրեստ-Լիտովսկի պայմանագրին։ Օսմանյան կայսրությունը շարունակեց առաջխաղացումն Անդրկովկասում և 1918 թ. հունիսի 4-ին Վրաստանի, Ադրբեջանի և Հայաստանի հանրապետություններին պարտադրեց շատ ավելի ծանր Բաթումի պայմանագիրը, որտեղ հայտարարվեց Նախջիևանը թուրքական բանակով բռնանվաճելու մասին։ Թեև հայ ազգային հերոս, գեներալ-մայոր Անդրանիկ Օզանյանը մերժեց Բաթումի պայմանագիրը և 1918 թ. հունիսի 7-ից մինչև հուլիսի 20-ը կատաղի կռիվներ մղեց թուրքերի դեմ, բայց նրա Հայկական առանձին հարվածող զորամասին չհաջողվեց Պարսկաստանում միանալ բրիտանական զորքերին կամ թուրքերից փրկել Նախիջևանի հայությանը։ Զորամասը 1918 թ. հուլիսի 23-ից մինչև նոյեմբերի 28-ը Զանգեզուրում էր և կարողացավ այս երկրամասը փրկել օսմանյան ներխուժումից ու կոտորածից։ Տեղի մահմեդական բնակչությունը Նախջիևանում փորձ արեց 1918 թ. մարտին անկախություն հռչակել: 1919 թ. հունվարի 17-ին, թուրքական հսկողության ներքո, Շարուր-Նախիջևան-Սուրմալուում ստեղծվեց «Արասդայանի հանրապետությունը»։ Քանի որ «Արաքսի հանրապետությունը» չափազանց թույլ էր, այն փոխարինվեց մարիոնետային այլ՝ թուրքական սահմաններում հայտարարված ինքնավար միավորով։ Успешное турецкое наступление на Кавказском фронте 10 февраля 1918 г. привело к Брест-Литовскому договору от 3 марта 1918 г. Османская империя не придерживалась пунктов этого документа, продолжая свое наступление в Закавказье. 4 июня 1918 г. с новообразованными независимыми республиками Грузии, Азербайджана и Армении был заключен более тяжелый – Батумский договор. Его текст гласил об аннексии Нахиджевана турецкими войсками. Хотя и армянский национальный герой, генерал-майор А. Озанян обоснованно отверг Батумский договор и с 7 июня до 20 июля 1918 г. развернул боевые действия против турок, но его Армянский особый ударный отряд не смог объединиться с британскими войсками в Персии и спасти нахиджеванских армян от турок. В марте 1918 г. местное мусульманское население Нахиджевана попыталось установить независимость. Затем в Шаруре-Нахиджеване-Сурмалу была создана марионеточная «Арасдаянская республика» под турецким контролем. Поскольку «Аракская республика» была слишком слабой, она была заменена другой марионеточной, уже автономной единицей в турецких границах. The successful Turkish advance on the Caucasus Front from February 10, 1918, re-sulted in the Treaty of Brest Litovsk, signed on March 3, 1918. The Ottoman Empire did not respect this document, continued its advance into the Transcaucasia and concluded on June 4, 1918, much more heavy Treaty of Batum with newly-independent republics of Azerbaijan, Georgia and Armenia. Its text announced annexation of Nakhijevan by the Tur-kish forces. Their invasion had been fulfilled by the 36th, 11th and 33rd Divisions on July 10-19, 1918. Though the Armenian national hero and General Major A. Ozanian reasonably rejected the Treaty of Batum and waged his fights from June 7 till July 20, 1918, his Arme-nian Special Striking Detachment could not unite with the British troops in Persia or save the Nakhijevan Armenians from the Turks. On July 14, 1918 he subordinated this district to Soviet Russia, but without any support from the Red Army. His Armenian Special Striking Detachment of 1.400-3.000 men had to evacuate with 35.000 Western and local refu-gees. His further stay in Zangezur on July 23 – November 28, 1918, gave better results and saved the district from the Ottoman invasion and massacre. The local Muslim population first attempted its independence on March 7-25, 1918. Then it proclaimed in Sharur-Nakhijevan-Surmalu a puppet "Republic of Arazdayan" under the Turkish control on De-cember 5, 1918 – January 17, 1919. Since the "Republic of Araxes" could not stand Arme-nian demands, it was replaced by another puppet, now autonomous unit in the frontiers of Turkey, troops of which evacuated from Goghtan on November 25, 1918, and from the whole Nakhijevan on January 26, 1919. During this period the Republic of Armenia ap-pointed its commissar of the district on November 27, 1918, and established a Military Go-vernorship under General Major G. Shelkovnikian on January 14, 1919. On the insistence of British, it was replaces on January 26 by their own Military Governorship; so on Febru-ary 3, an agreement with the Republic of Armenia was signed and on February 10, 1919, the Armenian army was called back to the northern borders of the district.
Keywords: History; Political science